IDENTITAS VISUAL DAN PENERAPANNYA PADA SIGNAGE UNTUK KAWASAN WISATA EDUKASI - AHMAD ZAKIYY MAYMUN; WIRANIA SWASTY (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2018)
Tourist attraction is a destination place for recreation on weekends or holidays. One of tourist attractions in Bandung is Kampung Batu Malaksari as a case of this study. With the theme 'Education Tourism', visitors are expected to enjoy the beauty of nature as well as get the knowledge. However, visitors cannot recognize the visual identity of the tourist attraction because it is not aligned with the theme. Moreover, the lack of signage that provides information in text and visual presentation of directions to the place, directory map, prohibitory, and warning that makes visitors confused and often lost to the tourist area. Therefore, the visual identity and its application to signage is considered necessary. Data collection methods used were observations, interviews and questionnaires using matrix analysis as a method of analysis. The purpose of this study is expected to create a strong visual identity that shows educational tourism as well as informative signage. This case study is expected to improve the visual appeal inherent in the visitor's mind.Â Keywords: educational tourism; signage; visual identity